Finger millet-based muffin decreases insulin response in individuals with prediabetes in a randomised controlled trial. Issue 4 (28th February 2023) - Almaski, Ameerah; Coe, Shelly; Lightowler, Helen; Clegg, Miriam E; Thondre, Pariyarath Sangeetha
Abstract: Millet is a grain high in polyphenols and antioxidants, which are bioactive compounds known to influence blood glucose response. The aim of this study was to compare the effect of finger millet muffin and wheat muffin on glycaemic response (GR), insulin response (IR), gastric emptying (GE) and satiety in healthy individuals and people with prediabetes. In a single-blind randomised controlled crossover trial at Oxford Brookes Centre for Nutrition and Health, fifteen healthy individuals and fourteen individuals with prediabetes were recruited between May and December 2017. The participants' GR (3 h), IR (3 h), GE (4 h) and satiety (4 h) were measured before and after the consumption of muffins. A mixed method ANOVA was used to compare GE and the incremental AUC (iAUC) for GR and IR between the participant groups and muffins. There was a significant interaction between participants and muffins on IR iAUC at 180 min ( P = 0·042). A significant effect of muffins was found on the GR peak ( P = 0·013). The millet muffin decreased the GR peak and IR iAUC compared with the wheat muffin in participants with prediabetes. A significant interaction between participants and muffins for GE ascension time Tasc ( P = 0·017) was observed, with no effect of muffins on satiety AUC in the participant groups. This study suggested that polyphenol and fibre-rich finger millet may have the potential to influence the management of prediabetes.